Factores de riesgo asociados a preeclampsia de inicio tardío en el servicio de Gineco-obstetricia 2013 – 2017 en el Hospital Belén de Trujillo - Alvites Infantes, Carlos Alberto (2019)
Introduction: Preeclampsia is a frequent disorder in pregnancy, which leads to maternal and infant risk of variable morbidity and mortality, the late type is the most frequent, knowing the risk factors would help to diminish its presentation and complications. Objective: To establish the risk factors associated with late-onset preeclampsia in the gynecology-obstetrics service 2013 - 2017 at the Hospital Belén De Trujillo (HBT). Method: Case-control study where 124 medical records (62 cases with late-onset preeclampsia and 62 controls) of pregnant women attended in the gynecological-obstetrics service of the HBT between 2013 and 2017 were reviewed. The Odds Ratio (OR) was calculated for the bivariate analysis. and multivariate analysis was performed by logistic regression to establish the associated factors. Results: pregestational obesity and maternal age ≥35 years presented association in the bivariate analysis and were maintained as factors associated with late onset preeclampsia in the multivariate analysis (ORa: 2.59 and 3.02, respectively). Conclusion: Pregestational obesity and maternal age ≥35 years are risk factors associated with late onset preeclampsia.